The warm-up maximize performance and improve long-term athletic development - Jeffreys, Ian (Human Kinetics, 2019)
This book guides strength and conditioning professionals, personal trainers, and coaches through the process of constructing effective RAMP-based warm-ups. The RAMP protocol (Raise; Activate and Mobilize; and Potentiate) is a systems approach that ensures each element of the warm-up contributes positively to the next, allowing the whole to be far greater than the component parts. Unlike traditional warm-ups, the RAMP protocol considers the medium and longer-term development of the athlete. The book describes the science of the warm-up and provides guidelines for the practitioner to follow to maximize the effectiveness of the warm-up